Website Based Attendance Information System at Jasdam II Sriwijaya - Firanti, Nabilah (Formosa Journal of Applied Sciences, 2024)
Attendance is mandatory for employees. Jasdam II Sriwijaya still uses manual methods when carrying out the attendance process. Therefore, we need an employee attendance system that can manage data so that it can be done quickly, efficiently and accurately. The result of this independent study is a website-based employee attendance information system which includes managing attendance information. The method used is Waterfall which is arranged in five stages, namely 1) needs analysis, 2) system design, 3) writing program code, 4) program testing, 5) program implementation and maintenance. The subject of this service is a website-based attendance information system at Jasdam II Sriwijaya. So the result obtained is that the attendance process becomes more efficient. After carrying out this service activity, it has a positive impact on the employee attendance system.